ANALISIS HUBUNGAN DISPOSISI MATEMATIKA SISWA TERHADAP KEMAMPUAN KONEKSI MATEMATIKA SELAMA PANDEMI COVID-19 DI SMK N 1 SOSORGADONG - Misbatul Khairah Pohan; Muhammad Syahril Harahap; Eva Yanti Siregar (JURNAL MathEdu (Mathematic Education Journal), 2022)
Abstract This research was motivated by the presence of COVID-19 at the beginning of 2020 which had a tremendous impact on almost all fields, one of which was in the field of education. Based on this situation, the researcher is interested in describing the Analysis of the Relationship between Students' Mathematical Dispositions on Mathematical Connection Ability During the Covid-19 Pandemic at SMK N 1 Sosorgadong. The research method used in this study is descriptive research and the subjects in this study were class X students of SMK Negeri 1 Sososrgadong, questionnaires and mathematical connection test sheets were used to collect data. The results of the test data about students' mathematical connection abilities in class X-TKJ II of SMK Negeri 1 Sosorgadong included the "good" category according to table 4.3, the data analysis was carried out with an average value of 79.04. The results of the questionnaire statement response data given to students about the mathematical disposition of students in class X-TKJ II SMK Negeri 1 Sosorgadong included the "good" category according to table 4.1 contained in Chapter IV, the data analysis was carried out with an average value of 79.48. Based on the calculations carried out to test the established hypothesis, it can be concluded that the hypothesis is accepted based on the t-test with a significant level of 0.000 <0.05 so Ha is accepted. So it can be concluded that the average value of the students who tested the validating the test questions first to determine the quality of the questions was significant. So that there is a significant relationship between students' mathematical dispositions to students' mathematical connection abilities.